Developing an Early Academic Ability Model based on Parenting and Attachment Styles with the mediating role of executive functions in preschool children - Dadvar , Samaneh; Sadeghi Afjeh , Zohreh; Kochakentezar , Roya (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present study aimed to develop an early academic ability model based on parenting and attachment styles with the mediating role of executive functions in preschool children. Method: The study was cross-sectional and correlational, and its statistical population consisted of all mothers and female and male preschool children in Yazd in 2019. Among them, 700 (350 girls and 350 boys) were selected using the multi-stage cluster sampling method. The research tools included the Early Academic Ability Questionnaire by Wright & Martinez (1997), the Kinship Center Attachment Questionnaire (KCAQ) by Halpern & Kappenberg (2006), Baumrind’s parenting style questionnaire (1997), and Questionnaire Executive Function (BRIEF). SPSS-v23 and Lisrel-V8.8 were used to analyze data. Results: The research results indicated that there were significant relationships between executive function, parenting styles, early academic ability, and attachment styles (P=0.01). The structural model also indicated that early academic ability was fitted based on parenting and attachment styles in preschool children. Conclusion: According to the results, paying attention to the above-mentioned variables in designing appropriate treatments helps researchers and therapists of preschool children.